Interrelation of countries' developmental level and foreign direct investments performance / Šalių išsivystymo lygio ir tiesioginių užsienio investicijų veiklos sąveika - Toma Lankauskienė; Manuela Tvaronavičienė (Journal of Business Economics and Management, 2011)
The aim of this article is to formulate hypothesis about interrelation of countries' developmental level and foreign direct investments performance with reference to relevant scientific literature. Reviewed ample relevant scientific literature made a presumption to arise that the impact of FDI differs in developed, developing and underdeveloped countries, i.e. depends on level of development: developed countries benefit most, developing less and underdeveloped least. Countries to respective groups have been attributed according to their level of development and indicators chosen for the formulation of following hypotheses. The following indicators capable of reflecting FDI impact on enhancing wellbeing in unevenly developed countries (GDP, exports, inflation, population, life expectancy at birth, primary school pupils, infant mortality, total health expenditure per capita, total tax rate, Internet users, residential consumption of electricity) and differences between developed and underdeveloped countries in the fields of: economic, social and business environment. In the paper a series of hypotheses has been formulated.